Features of CO2 fracturing deduced from acoustic emission and microscopy in laboratory experiments - Ishida, T.; Chen, Y.; Bennour, Ziad; Yamashita, H.; Inui, S.; Nagaya, Y.; Naoi, M.; Chen, Q.; Nakayama, Y.; Nagano, Y. (AMER GEOPHYSICAL UNION, 2016)
©2016. American Geophysical Union. All Rights Reserved. We conducted hydraulic fracturing (HF) experiments on 170 mm cubic granite specimens with a 20 mm diameter central hole to investigate how fluid viscosity affects HF process and crack properties. In experiments using supercritical carbon dioxide (SC-CO2), liquid carbon dioxide (L-CO2), water, and viscous oil with viscosity of 0.051–336.6 mPa · s, we compared the results for breakdown pressure, the distribution and fracturing mechanism of acoustic emission, and the microstructure of induced cracks revealed by using an acrylic resin containing a fluorescent compound. Fracturing with low-viscosity fluid induced three-dimensionally sinuous cracks with many secondary branches, which seem to be desirable pathways for enhanced geothermal system, shale gas recovery, and other processes.